Introducing the Rhamphoriaceae, fam. nov. (Sordariomycetes), two new genera, and new life histories for taxa with Phaeoisaria- and Idriella-like anamorphs - Réblová, Martina; Štěpánek, Václav (Mycologia, 2018)
Two new genera, Rhamphoriopsis and Xylolentia, are described for lignicolous perithecial ascomycetes occurring in terrestrial habitats. Fresh material, living cultures, morphology, and DNA sequence data (nuc rDNA internal transcribed spacers [ITS1-5.8S-ITS2 = ITS], 18S and 28S genes, and second largest subunit of RNA polymerase II = RPB2) of these taxa and morphologically similar fungi were studied to determine their relationships. A monophyletic clade including Rhamphoria, Rhodoveronaea, a dematiaceous hyphomycete Linkosia multiseptum, and the two new genera was recovered in the Sordariomycetes based on the 18S-28S-RPB2 data set. It is introduced as the family Rhamphoriaceae and strongly supported by Bayesian and maximum likelihood methods. Its members are characterized by perithecial ascomata with a cylindrical or rostrate neck, the absence of stromatic tissue or clypeus, similar anatomy of two-layered ascomatal walls, cylindrical paraphyses, unitunicate asci with a distinct, nonamyloid apical annulus, and dictyoseptate or transversely septate, hyaline or brown ascospores. The mode of conidiogenesis is holoblastic, predominantly on polyblastic-denticulate conidiogenous cells. The Phaeoisaria-like anamorph has been linked to Rhamphoria and Rhamphoriopsis, whereas conidia and conidiophores of Idriella-like synanamorph were formed in vitro in two species of Rhamphoria. The Veronaea-like anamorph is associated with Rhodoveronaea. The anamorph of Xylolentia is a dematiaceous hyphomycete with conidiogenous cells with sympodially extending rachis. A key to members of the family is provided. The classification and nature of species boundaries in Rhamphoria are discussed, and diagnostic characters such as ascospore shape, number of transverse and longitudinal septa, a degree of constriction at the septa, and ability to produce ascoconidia are evaluated.
Keywords: Base Sequence; Ascomycota; ribozomální DNA; DNA, Ribosomal; 5 new taxa; budding ascospores; Xylariales; multigenová rodina; wood-inhabiting fungi; Bayesova věta; DNA, Fungal; Bayes Theorem; Phylogeny; multigene phylogenetic analysis; RNA-polymerasa II; sekvence nukleotidů; Spores, Fungal; RNA Polymerase II; Sequence Analysis, DNA; ekosystém; DNA fungální; Ecosystem; sekvenční analýza DNA; fylogeneze; spory hub; Multigene Family